Implementation Strategy for the Real-Time Financial Crisis Early Warning System for Profit Optimization at Permata Bunda Syariah Clinic Cirebon - Zulkifli Ahmad; Rian Andriani; Kahar Mulyani (Ann Publisher, 2026)
Background. Financial uncertainty and cash flow dynamics in healthcare facilities require an early warning system that can detect potential financial distress quickly and accurately. PBSC Clinic, as a healthcare institution, faces financial risks stemming from fluctuations in revenue, operating expenses, and short-term and long-term liabilities. Therefore, the development of the Real Time Clinic's Financial Crisis Early Warning System (RT, CFC, EWS) is important as a managerial decision-making tool based on actual financial data. Purpose. This study aims to analyze the financial condition of PBSC Clinic and to develop a CFC EWS RT based on profitability, liquidity, leverage, and distance-to-default indicators, presented in a real-time dashboard. Method. This type of research is an evaluative-descriptive study with a case study approach. The data used are the financial statements of the PBSC Clinic for the current period, which are analyzed using financial ratios and risk zone mapping (green, yellow, red) as early warning signals. Results. The results of the study show that the CFC EWS RT dashboard can represent the clinic's financial condition in an accurate and contextual manner. This system is effective at providing an early signal of declining profitability, liquidity pressures, and increased leverage risk, allowing management to take corrective action in a relatively short time. Conclusion. RT CFC EWS plays a strategic role in supporting the financial stability and sustainability of the PBSC Clinic. Implications. Practically, this research provides implementable guidance that can be directly used by the management of PBSC Clinics and similar health facilities. The CFC EWS RT Dashboard is capable of being a simple but effective daily monitoring tool.